Copper catalyzed oxidative deamination of Betti bases: an efficient approach for benzoylation/formylation of naphthols and phenols. Issue 46 (22nd April 2016) - Deb, Mohit L.; Pegu, Choitanya Dev; Borpatra, Paran J.; Baruah, Pranjal K.
Abstract : A copper-catalyzed benzoylation/formylation of naphthols and phenols via oxidative deamination of Betti bases. Abstract : An efficient route for benzoylation or formylation of naphthols/phenols is developed via oxidative deamination of Betti bases. A copper salt catalyst with TBHP as an oxidant is used. Water is used as a reagent as well as solvent. The reaction proceeds through a regioselective radical pathway. Most importantly, the position of acylation is unambiguous. The method is also applicable to non-hydroxy substrates.